Od glasbenih slovnic h kogniciji glasbe v osemdesetih in devetdesetih letih 20. stoletja - Schüler, Nico (Muzikološki zbornik, 2007)
While approaches that had already established historical precedents - computer-assisted analytical approaches drawing on statistics and information theory - developed further, many research projects conducted during the 1980s aimed at the development of new methods of computer-assisted music analysis. Some projects discovered new possibilities related to using computers to simulate human cognition and perception, drawing on cognitive musicology and Artificial Intelligence, areas that were themselves spurred on by new technical developments and by developments in computer program design. The 1990s ushered in revolutionary methods of music analysis, especially those drawing on Artificial Intelligence research. Some of these approaches started to focus on musical sound, rather than scores. They allowed music analysis to focus on how music is actually perceived. In some approaches, the analysis of music and of music cognition merged. This article provides an overview of computer-assisted music analysis of the 1980s and 1990s, as it relates to music cognition. Selected approaches are being discussed.
Keywords: glasba; glasbene slovnice; kognicija; music; psihologija; psychology; računalniška analiza